Solid Dispersions for Drug Delivery Applications and Preparation Methods - Khutoryanskiy, Vitaliy; Al-Obaidi, Hisham (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Since their first application in the improvement of solubility of orally delivered drugs, applications of solid dispersions have considerably expanded to include cancer, infections, and inflammatory conditions. This book presents recent advancements in the development and use of solid dispersions for different therapeutic applications. This book can be particularly useful for researchers as well as postgraduate students in formulation sciences and drug delivery. Undergraduate students will also find elements of this book very relevant to scientific fundamentals such as solubility and crystallization of amorphous materials as well as drug delivery challenges.